Proverbs: 8:22-25 in the Context of the Antiarian Polemics of St. Athanasius' Second Oration against the Arians - Rusev, Rosen (Forum Theologicum Sardicense, 2025)
Rosen Rusev, Proverbs: 8:22-25 in the Context of the Antiarian Polemics of St. Athanasius' Second Oration against the Arians. The main topic of the present essay is the interpretation of Proverbs 8:22-25, written by St. Athanasius of Alexandria in his Second Oration against the Arians. Among the issues taken into consideration is the identification of the literary genre, the explication of the text structure and the lexicological and philological analysis by the Alexandrian bishop. Because of his ingenious exegesis of the aforementioned Biblical text St. Athanasius achieves to change the context, transferring its application and meaning from the field of the pure Theology to the field of the divine Economy of salvation. In this way he refutes the Arian misunderstanding of the text.